THE ROLE OF LAND AND URBAN RURAL BUILDING TAXES IN PEKALONGAN - Maulana, Wahyu Sultan; Cahayaningtyas, Dyah Ayu Septi; Wicaksono, Galih; Safitri, Deviana; Al–Mukhlishin, Mu’min (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
Through fiscal policies provided by the central government to regional governments, regional governments have the authority to regulate and administer their economy by regulating expenditure and receipts. Urban Rural Land and Building Tax levies (PBB-P2) are regulated by the regional government in accordance with Law Number 28 of 2009 concerning Regional Taxes and Regional Retributions (PDRD). This research is aimed at finding out the effectiveness and contribution of the role of Rural-Urban Land and Building Tax (PBB-P2) revenue to Pekalongan Regency’s original regional income (PAD). This research uses descriptive qualitative methods. This research takes secondary data found on the Pekalongan Regency Central Statistics Agency website. The data taken is target data and realization of Rural Urban Land and Building Tax revenues as well as realization of Regional Original Income (PAD) revenues in Pekalongan Regency for 2019-2021. The results of this research show that the effectiveness of the Rural and Urban Land and Building Tax in Pekalongan Regency from year to year still appears to be effective. Meanwhile, the contribution from the Urban and Rural Land and Building Tax is still less helpful every year